Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T19:51:58+01:00
A) 3b+(b+1)=3b+b+1=4b+1
b) 5a-(a+1)5a-a-1=4a-1
c) 2x-(3-5-x)=2x-3+5+x=3x+2
d) 2a+(3a-2b)+(a+b)=2a+3a-2b+a+b= 6a-b
e) 5a-(2-x)+b-2x+5= 5a-2+x+b-2x+5= 5a+b-x+3
f) 7k-(m-2n+k)-(5k-3)+(2k-1)= 7k-m+2n-k-5k+3+2k-1= 6k -3 + 2n+2=6k+2n-1
2010-03-11T19:56:12+01:00
A) 3b+(b+1)= 3b+b+1= 4b+1
b)5a-(a+1)= 5a-a-1= 4a-1
c) 2x-(3-5-x)=2x-3+5+x= 3x+2
d) 2a+(3a-2b)+(a+b)= 2a+3a-2b+a+b=6a-b
e) 5a-(2-x)+b-2x+5=5a-2+x+b-2x+5=5a+3-x+b
f) 7k-(m-2n+k)-(5k-3)+(2k-1)= 7k-m+2n-k-5k+3+2k-1=8k-m+2n+2

Liczę na naj ;-)